Contrasting Colonist and Indigenous Impacts on Amazonian Forests - LU, FLORA (2010)
To examine differences in land use and environmental impacts between colonist and indigenous populations in the northern Ecuadorian Amazon, we combined data from household surveys and remotely sensed imagery that was collected from 778 colonist households in 64 colonization sectors, and 499 households from five indigenous groups in 36 communities. Overall, measures of deforestation and forest fragmentation were significantly greater for colonists than indigenous peoples. On average, colonist households had approximately double the area in agriculture and cash crops and 5.5 times the area in pasture as indigenous households. Nevertheless, substantial variation in land-use patterns existed among the five indigenous groups in measures such as cattle ownership and use of hired agricultural labor. These findings support the potential conservation value of indigenous lands while cautioning against uniform policies that homogenize indigenous ethnic groups.